The Role of Imam Azam Abu Hanifa in Hadith Narration - Rouhani, Muhammad Osman; Mazhari, Abdul Qodus (Diwan, 2025)
The present study, entitled “The Role of Imam Abu Hanifa in Hadith Narration,” aims to investigate the significant contributions of Imam Abu Hanifa (may Allah have mercy on him) in both the narration and understanding of Hadith. This article addresses prevailing doubts expressed by some critics who question his scholarly role in the transmission of Hadith. While numerous scholars have explored his literary, juristic, and exegetical contributions, the findings of this research demonstrate that Imam Abu Hanifa was not only an outstanding jurist skilled in ijtihad (independent legal reasoning) but also held a distinguished position among Hadith scholars. The perception of his weakness in Hadith narration, held by certain Hadith experts, largely results from limited knowledge of his biography or sectarian biases. This study concludes that Imam Abu Hanifa was among the Tabiyn (the generation following the Companions) and a prominent teacher of Hadith. His preserved works, notably the Musnad of Imam Abu Hanifa, substantiate this claim. The research employs a descriptive-analytical methodology, critically examining authoritative Hadith collections and historical sources. It also reviews prior scholarly works on the subject and adheres to international research standards. The article comprises an abstract, introduction, findings, conclusion, and a comprehensive reference list. Bu araştırma, "İmam Ebu Hanife'nin Hadis Rivayetindeki Rolünün İncelenmesi" başlığı altında hazırlanmıştır. Bu araştırmanın amacı, İmam-ı Azam Ebu Hanife'nin, hadis ilmî ve rivayeti konusundaki hedis alimlerinin nezdindeki rolünü tanımaktır. Bu makale, İmam-ı Azam Ebu Hanife'nin hadis rivayetindeki ilmî rolünü inkâr edenlere karşı cevaplar sunmaktadır. İmam Ebu Hanife'nin ilmî, ictihadî ve fıkhî eserleri hakkında birçok kitap yazılmıştır. Bu araştırmanın bulguları, İmam Azam Ebu Hanife'nin sadece fıkhî meselelerin çıkarılması ve istinbatında yeterli bilgi ve yeteneğe sahip olmadığını, aynı zamanda hadis ilmi ve rivayetinde de büyük bir konumda olduğunu göstermektedir. Bazı hadisçilerin, İmam Ebu Hanife'yi zayıf görmekteki tutumu, ya hayatı hakkında yeterli bilgiye sahip olmamaları ya da mezhebi taassup yüzündendir. Bu araştırma, İmam Ebu Hanife'nin, tabiînin önde gelenlerinden ve büyük hadisçilerden biri olduğunu ortaya koymaktadır. Onun geriye kalan ilmî eserleri, örneğin "İmam Ebu Hanife'nin Musned’i" bu iddiayı doğrulamaktadır. Bu araştırma, analitik ve tanımlayıcı bir yöntemle, güvenilir hadis ve tarihî kitaplar değerlendirilerek yapılmıştır. Araştırma sürecinde, konuyla ilgili geçmişte yapılmış ilmî çalışmalar gözden geçirilmiştir. Bu yazıda, araştırma için uluslararası bilimsel ölçütler gözetilmiştir. Makale, özet, giriş, bulgular, sonuçlar ve kaynakça listesi içermektedir. تحقیق حاضر با عنوان «بررسی نقش امام اعظم ابوحنیفه در روایت حدیث» به بررسی یکی از موضوعات مهم در حوزه علم حدیث پرداخته و تلاش دارد نقش و جایگاه امام ابوحنیفه رحمه الله را در نقل و روایت احادیث نبوی تبیین نماید، هدف این تحقیق شناخت نقش  امام اعظم ابوحنیفهرحمه الله نزد محدثین در علم درایت و روایت حدیث می‏باشد. این مقاله پاسخ شبهات منکرین، نقش علمی امام ابوحنیفه رحمه الله در روایت حدیث را تبیین می‏کند، در مورد نقش‏علمی، اجتهادی و آثار فقهی امام ابوحنیفه به صورت عمومی کتاب‌های زیادی تحریر گردیده است. یافته‌های این تحقیق نشان می‏دهد که امام اعظم ابوحنیفه رحمه الله نه‌تنها در استنباط و استخراج مسائل فقهی درایت و مهارت کافی داشته؛ بلکه ایشان در علم روایت و درایت حدیث نیز از جایگاهی بزرگی برخوردار بوده و ضعیف دانستن امام صاحب از طرف برخی محدثین به دلیل عدم آگاهی از احوال زندگی ایشان و یا تعصب مذهبی است. در تحقیق هذا به این نتیجه می‌رسیم که امام ابوحنیفه رحمه الله در زمرهٔ تابعین و از جمله استادان بزرگ محدثین شمرده می‌شود، آثار علمی باقی‌مانده از ایشان مانند مسند امام ابی‌حنیفه، شاهد این مدعی است. این تحقیق به روش تحلیلی- توصیفی با تکیه ارزیابی کتاب‌های معتبر حدیثی و تاریخی انجام شده و در  تحقیق فوق از آثار علمی گذشته مرتبط به موضوع تحقیق مرور شده است. در این نوشتار معیارهای علمی تحقیق رعایت گردیده است.